Analysis and Design of Intersection for Improved Traffic flow at Awolowo Junction, Bodija Ibadan, Nigeria (2019)
Traffic Congestion is inevitable for residents of economically dynamic cites therefore city authorities have to devise means of managing congestion to ease commuters of constrains imposed upon them by traffic congestion. The need for improvement of traffic flow at Awolowo Junction Bodija Ibadan is germane due to traffic congestion at this intersection. The aim of this study is to improve traffic flow at Awolowo Junction Bodija Ibadan. Traffic survey was carried out at the intersection, the peak hour factor and the design hourly volume were determined then the saturation flow rate and the cycle length (using the concept of volume-to-capacity ratio) were determined following the steps outlined in the Highway Capacity Manual, thereafter the yellow interval and the green times were computed. The peak hour was between 4:00 pm - 5:00 pm with a flow of 2989 vehicles per hour and a factor of 0.94 with design hourly volume of 539, 1464 and 1177 vehicles per hour for North, West and East approach respectively. The data collected was checked against the traffic signal warrants of the Manual on Uniform Traffic Control Device and yielded positive result with warrant 3. The saturation flow rate was computed to be 2618, 4320 and 3913 vehicles per hour for the North, West and East approach respectively with a flow ratio of 0.21, 0.34 and 0.3 for North, West and East Approach respectively. A pre-timed traffic control signal was designed to improve traffic flow at Awolowo Intersection of UI/secretariat Road.